The Guritan of Radin Suane : a study of the Besemah oral epic from South Sumatra - Collins, William A., (Bibliotheca Indonesica ;, 1998)
This study presents the text and translation of an oral epic, or guritan , relating the exploits of Radin Suane, which was recorded during anthropological fieldwork among the Besemah, in the remote highlands of South Sumatra. Documentation of an epic in Besemah, a little known Sumatran-Malay language, will be useful for comparative purposes to specialists in Malaysian and Indonesian languages and literatures. This work is also intended to serve students of ethnography, folklore and oral poetry, as well as general readers who may not be familiar with Sumatran culture. Accordingly, an extensive commentary has been provided to give a cultural context for understanding this epic.